Transapokaliptika: “Setelah-Kiamat” Tidak Ada Kajian Budaya - Siswanto, Zuhdi (Retorik: Jurnal Ilmu Humaniora, 2025)
This paper examines Cultural Studies from a historical perspective, emphasizing its role as an intellectual project that emerges from social crises and structural antagonisms. Spanning its development from the 1960s to the contemporary period (1990–2025), the paper shows that neoliberal capitalism is not merely an economic project, but one that has also permeated education, healthcare, religion, art, and everyday life, forming circuits of commodification and capital accumulation. In response to discourses on global ecological crisis, Cultural Studies is framed not as a passive academic discipline, but as an interdisciplinary practice that thrives on contradiction, understanding “apocalypse” not as a singular event but as a historical, simultaneous, and rhizomatic condition that shapes human experience in the era of globalization and platform capitalism. Introducing “transapocalyptic” as a term for a comprehensive crisis produced by neoliberalism’s penetration into all spheres of life, this paper rejects the notion of a “post-apocalypse” by positioning it as a utopia construct. Accordingly, Cultural Studies functions as a tool for reflection and critique that enables survival amid contemporary social, ecological, and symbolic crises while reminding us that the journey toward a fully emancipatory order is always “not yet”, for beyond utopia, a truly “post-apocalyptic” world does not exist.